Addressing the Mental Health Needs of Older People in Prison: Development of an Initial Programme Theory (IPT) Based on Realist Synthesis - Lee D. Mulligan; Deborah Buck; Falaq Ghafur; Joshua Southworth; Matilda Minchin; Jenny Shaw; Jane Senior; Katrina Forsyth (Mental Health Science)
ABSTRACT The mental health needs of older people in prison (OPiP) are considerable but remain overlooked. This review aimed to develop an Initial Programme Theory (IPT) to understand how the mental health needs of OPiP can be addressed and how mental health care for older people in the community could be adapted for the prison environment. A review and realist synthesis pertaining to the mental health needs of OPiP was conducted across three stages, including: (1) a systematic review of empirical work; (2) a scoping review of prison guidance documents; and (3) a scoping review of community mental health guidance documents. Synthesis of eligible literature and development of the IPT followed realist principles and was supplemented by a stakeholder workshop of experts by personal and occupational experience. Overall, 122 sources were included. The IPT suggested that prisons can address the mental health needs of OPiP via micro‐level mechanisms (i.e., screening, assessment, care planning, intervention, continuity of care/release), meso‐level mechanisms (i.e., accommodation, environment, activities, religion/spirituality, peer support, family support) and macro‐level mechanisms (i.e., staff training/education, governance). Each mechanism is underpinned by trauma‐informed, integrated and patient‐centered care principles and their implementation should be guided by a local assessment of prison‐specific needs. Our IPT provides a framework for how prisons can address the mental health needs of OPiP, informed by community care provision, via several mechanisms across different levels. Future research should build on this work to inform a full evaluation of its impact on meaningful outcomes to promote equivalency of care for OPiP and non‐discriminatory access to mental health support for those at risk of marginalization.